Affirmation Education Program: Bridging the Gap between Inclusion and Integration for Migrant Students - Anggara, Dio (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2023)
Migrant students face unique challenges and obstacles in their educational journey, particularly in terms of social support and overall well-being. This study aims to examine the relationship between social support and the well-being of migrant students participating in the Affirmation of Education Program (ADik) in Papua and the 3T Regions. Using a quantitative approach, data was collected from a sample of 34 active students through surveys and in-depth interviews. The study employed non-probability sampling, ensuring equal opportunity for 66 eligible students. The collected data was analyzed using SPSS, and the instrument's reliability and validity were established through pretesting. The results indicated that migrant students' well-being scores were particularly low in the area of mental well-being. Regression tests revealed that emotional support, network support, and informational support significantly influenced student well-being, while reward support and instrumental support showed no effect. Additionally, the network of religious groups and student diversity were found to play a role in determining student welfare. These findings underscore the importance of social support interventions targeting emotional support, networking, and information to enhance the well-being of migrant students in the ADik program in Papua and the 3T regions. Future programs and policies should prioritize the development of these aspects to improve the overall welfare of migrant students. This study contributes to our understanding of the challenges faced by migrant students and emphasizes the need for inclusive educational initiatives that address their social support needs and promote their well-being